Pengaruh Self Efficacy terhadap Kinerja Karyawan dengan Kepuasan Kerja sebagai Variabel Intervening (Studi PT. Ultrajaya Milk Industry, Tbk Surabaya Bagian Marketing) - Fauzan Ali; Dewie Tri Wijayati Wardoyo (Jurnal Ilmu Manajemen, 2021)
The purpose of this research is to test and analyze the role of Job satisfaction as an intervening variable between self-efficacy and employee performance. Research object at PT. Ultrajaya Milk Industry, Tbk Surabaya area, is the marketing department. Several factors that can improve employee performance are the employees' sense of security and comfort in the work environment. This research is using a quantitative approach. The population in this study are 56 employees at PT. Ultrajaya Milk Industry, Tbk in Surabaya Area. The data analysis technique used Structural Equation Model Partial Least Square with software SmartPLS version 3.0. The technique of collecting data using questionnaires and interviews. The result showed that self-efficacy has no significant effect on employee performance. Self-efficacy has a positive and significant effect on job satisfaction. Job satisfaction has a positive and significant effect on employee performance. Job satisfaction as an intervening variable affects the relationship between self-efficacy and employee performance at PT. Ultrajaya Milk Industry, Tbk in Surabaya Area, is the marketing department. This study implies that if the company wants to improve employee performance, then employee job satisfaction must be realized, maintain a comfortable work environment, and provide motivation to training to maximize and increase self-efficacy.